An empirical study of the post-experiential growth of military personnel – combatants - V. O. Oliinyk; S. O. Larionov (Bulletin of Kharkiv National University of Internal Affairs)
The need to find innovative technologies for psychological recovery and rehabilitation of servicemen – combatants, taking into account the positive personal changes that can develop as a result of their experience of traumatic and non-traumatic (negative stressful) events in a combat situation, led to the choice of the research topic. The purpose of the study is to examine the relationship between the post-experiential growth of servicemen and women combatants and their life and combat experience.